Metal accumulation in juvenile and sub-adult loggerhead and green turtles in northern Cyprus - Celik, Sude; Beton, Damla; Cicek, Burak Ali; Snape, Robin T. E.; Baskale, Eyup (Elsevier Sci Ltd, 2023)
Sea turtles are considered pollution bioindicators due to their tendency to accumulate high metal levels in their tissues during their long lifespans. In this context, we aimed to analyse the concentrations of 12 elements in liver, kidney, heart and muscle samples from green turtles (Chelonia mydas; n = 41) and loggerhead turtles (Caretta caretta; n = 14) found stranded in Northern Cyprus. The samples were collected between 2019 and 2021, stored in sterile Eppendorf tubes at -20 degrees C until metal analysis, and analysed with an inductively coupled plasma mass spectrometer. With this study, we contribute to the limited number of studies on metal accumulation in heart tissue and present the first data for Mg accumulation in the heart, liver, muscle and kidney tissues of both species. We found that metal accumulation levels differed among the two study species' tissues, with some elements in the same tissue (Al-Kidney, As-Heart, As-Liver, Fe-Muscle, Fe-Kidney, Fe-Heart, Mn-Heart, Pb-Heart, Zn-Muscle and Zn-Kidney) significantly differing between species. The observed variation likely resulted from their different feeding habits, which cause them to be exposed to different levels of metals. We also found significant associations among elements within tissues, as well as between the same element across different tissues in both species, which may indicate the differential accumulation of elements among organs due to physiological processes in turtle metabolism, bioaccumulation or excretion.
Keywords: Sea turtles; Trace elements; Elemental associations; Northeastern mediterranean sea; Organs; Bioaccumulation; Pollution